Selected variations of the organic anion transporting polypeptide 2 (OATP2) gene in Malay neonates with and without hyperbilirubinaemia - Nawawi, Noor Namirah (2015)
Neonatal hyperbilirubinaemia is caused by many possible risk factors, including genetic factor. The OATP2 protein, which is encoded by OATP2 gene plays a crucial role in transporting bilirubin from the circulation to the hepatocytes. There are several genetic variations that have been reported and each of them was presence at different frequencies between population to population. The role of genetic variations of the OATP2 gene in the development of neonatal hyperbilirubinaemia is still controversial and there is lack of study investigated the association between the presence of genetic variations and neonatal hyperbilirubinaemia including in Malay population in Malaysia. The appropriate choice of screening method is also important to allow robust and accurate genotyping results. The objectives of this study is to screen for the selected genetic variations of the OATP2 gene using high resolution melting (HRM) analysis, to determine the genotype, allele as well as haplotype frequencies between hyperbilirubinaemia and non-hyperbilirubinaemia groups and to determine the association between genotypes and haplotypes with the development of neonatal hyperbilirubinaemia. Buccal cells sample of 264 neonates were collected and DNA was extracted using commercialized DNA extraction kit. HRM analysis was performed to screen for the selected genetic variations and samples that have different pattern of melt curve were confirmed by DNA sequencing analysis. Out of 14 genetic variations that were selected, 9 were presence in Malay neonates with the most common is c.388 A>G.This study also shows that there was no significant association between genetic variations of the OATP2 gene with neonatal hyperbilirubinaemia in Malay neonates except for heterozygous mutant genotype of c.597 C>T that shows high frequency in non-hyperbilirubinaemia group. The analysis on the association between serum bilirubin levels and genotypes found there was a significant association of g.-11187 G>A with serum bilirubin levels. However, the analysis on the association between serum bilirubin levels and haplotypes of other genetic variations shows no significant differences. Thus, further study need to be conducted for confirmation.